Fabrication of Doxycycline–Nigella Sativa-Eugenol (DNE) emulsion intended for local treatment of chronic periodontitis - Nurhani Emira Hamidon (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2020)
Locally applied antibiotic in periodontal therapy offers a low-cost, non-invasive procedure with potential to maximise therapeutic efficacy with a low drug dosage regimen. In this study, newly fabricated doxycycline hyclate (DH) emulsions which differ in the amount and type of emulsifiers (lecithin and hydroxypropyl methylcellulose) were thoroughly assessed for their compatibility, characterisation and analytical method. The compatibility assessment employed differential scanning calorimetry (DSC) and attenuated total reflectance – Fourier transform infrared spectroscopy (ATR – FTIR). The emulsions were subjected to phase separation and accelerated stability studies and characterised for droplet size, polydispersity index (PDI) and zeta potential using a nanosizer. Additionally, viscosity and rheological behaviour were also evaluated using a rheometer. An analytical method using HPLC was then developed and validated to quantify doxycycline from the emulsion. A UV-spectrophotometry was also developed and validated and used to quantify release behaviour. It was found that all excipients tested were compatible with each other. Compatibilities of DH with all excipients incorporated in the emulsion were indicated by the consistent thermogram of the DH as shown by DSC for binary mixtures (DH-excipients) of which the excipients tested were sodium propyl paraben, sorbitan monooleate, lecithin, Nigella sativa oil, hydroxypropyl methylcellulose, polysorbate 80, sodium methyl paraben and eugenol. The emulsions were also highly stable as there was absence of phase separation after being challenged with centrifugation at 4000 rpm for 15 minutes. Stability was indicated further by the zeta potential values of between -48.2±0.4 to -64.0±3.9. In addition, droplet size was within the range of 198.6±8.2 to 279.3±10.7 nm. The emulsions were also highly polydisperse as PDI value falls between 0.448±0.026 to 0.710±0.080. An increasing and improving pattern of viscosity and rheological behaviour was observed as the concentration of the emulsifiers was increased. The recovery of the doxycycline was found to be 98.2±2.2 % indicating that the purity of the API was maintained following combination with excipients. The in vitro release pattern was conducted using dissolution tester and analysed by UV-spectrophotometry module. The release profile showed a prolonged release (5 hours) in the lecithin stabilized emulsion as compared to lecithin-HPMC stabilized emulsion (2 hours). In conclusion, the stable fabricated emulsion was expected to provide promising therapeutic efficacy as a new locally applied antibiotic for the treatment of periodontitis. Keyword: Doxycycline hyclate, periodontitis, local drug delivery, emulsion